2008
DOI: 10.1097/icu.0b013e3282f154bd
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery for the developing world

Abstract: Treating cataract blindness worldwide continues to be a formidable challenge. Significant barriers include cost, lack of population awareness, shortage of trained personnel and poor surgical outcomes. Both phacoemulsification and manual small incision extracapsular cataract surgery achieve excellent visual outcomes with low complication rates, but manual small incision extracapsular cataract surgery is significantly faster, less expensive and requires less technology. Therefore, manual small incision extracaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
159
4
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(180 citation statements)
references
References 29 publications
1
159
4
9
Order By: Relevance
“…Among these disorders, cataract is the leading cause of blindness worldwide and accounts for estimated cases of 18 million, half of all these cases originating in developing countries (6,7). Several large-scale population-based epidemiological studies consistently revealed strong links between obesity and cataract (5,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Among these disorders, cataract is the leading cause of blindness worldwide and accounts for estimated cases of 18 million, half of all these cases originating in developing countries (6,7). Several large-scale population-based epidemiological studies consistently revealed strong links between obesity and cataract (5,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…A cirurgia de catarata é o procedimento cirúrgico oftalmológico mais comumente realizado no Brasil, sendo a facoemulsificação a técnica mais utilizada devido a diversos fatores como possibilidade de microincisão tunelizada com aplicação de lente intraocular (LIO) dobrável (diminuindo astigmatismo induzido), menor tempo cirúrgico e dano corneoendotelial, possibilitando uma recuperação pós-operatória mais rápida (1)(2)(3)(4) . Portanto, um treinamento qualificado da técnica deve ser um dos principais objetivos de qualquer programa de residência de oftalmologia.…”
Section: Discussionunclassified
“…É a principal causa tratável de cegueira em todo o mundo (1)(2)(3)(4) . Segundo a Organização Mundial de Saúde, há 45 milhões de cegos no mundo, dos quais 40% são devidos à catarata (5) .…”
Section: Introductionunclassified
“…1,2 Cataract surgery often achieves excellent visual outcomes with low rates of complication. 3,4 However, in LMICs, cataract surgical coverage is often low, and visual outcomes may be poor, 1,[5][6][7][8] especially owing to operative complications and uncorrected refractive errors, both of which require postoperative follow-up for diagnosis and treatment. 4,[8][9][10][11][12] Unfortunately, even shortterm (<6 weeks) follow-up rates after cataract surgery are less than 50% in many regions in LMICs and may fall below 30%.…”
mentioning
confidence: 99%